2006
DOI: 10.1002/ar.b.20103
|View full text |Cite
|
Sign up to set email alerts
|

Study pace as a factor that influences achievement in a human anatomy course

Abstract: Determining the optimal conditions for learning anatomy will help medical students to do better in a gross anatomy course. We examined the two types of anatomy courses offered in our institution: slow-paced (SP) and fast-paced (FP) courses, in which the same content is taught in approximately the same number of hours (SP ‫؍‬ 91 hr; FP ‫؍‬ 90 hr), but the duration of each course differed (SP ‫؍‬ 91 1-hr sessions lasting 20 weeks; FP ‫؍‬ 45 2-hr sessions lasting 9 weeks). The objective of this study was to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, the results also revealed that the pace of the study was less stimulating. The literature has shown that the achievements get worse as the pace of the course increases, and this fast-paced course can reduce the motivation of the students and also increase their stress (29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results also revealed that the pace of the study was less stimulating. The literature has shown that the achievements get worse as the pace of the course increases, and this fast-paced course can reduce the motivation of the students and also increase their stress (29).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that there is no significant difference between the grades of first-time students in the gross anatomy regular course and remedial students, despite the latter having already been exposed to the course material. Repeating the gross anatomy course is not considered an academic advantage (Elizondo-Omañ a et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…This is often not a problem for senior level students who have previously taken Organic Chemistry I and II, Calculus, Physics I and II, as well as demanding upper level biology and chemistry courses. However, sophomore and junior level students often struggle with the study pace of anatomy (Elizondo-Omana et al 2006). Moreover, many undergraduates, even senior level students, may have very poor study and time management skills.…”
Section: Challengesmentioning
confidence: 99%